Transboundary debris in Indonesian frontier and outermost island: A preliminary case study of Nipah Island - Muhammad Reza Cordova; Triyoni Purbonegoro; Rachma Puspitasari; Riyana Subandi; Muhammad Taufik Kaisupy; Singgih Prasetyo Adi Wibowo; Nurjamin; Suparmo; Serly Sapulete (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Anthropogenic debris in marine pollution is one of the significant environmental problems. The objective of the research was focused on the abundance and the distribution of debris found on Nipah Island,Riau Island Province, which was surveyed at ten sampling points, as a preliminary monitoring. Abundance and distribution were estimated with line transect of 50m x 3m. Debris items were categorized by the type of material from the NOAA Marine Debris Program. The abundance and weight calculated each of the types, and simple identification of country supplier also determined from the labels of the plastic. The result showed the average debris abundance of 7.05±6.71 items/m2 and an average weight of 1.67±3.98 kg/m2. The most debris abundance found in every station were plastic (single-use plastic bottle/cup), lumber, metal, and glass. Stranded lumber was the dominant weighted samples, followed by plastic debris. Approximately 51.60% of total plastic (food wrappers) with identifiable labels were from Malaysia (24.26%), Indonesia (23.68%), Singapore (2.33%), and elsewhere (1.33%). In order to manage transboundary debris, science is the primary point to obtain proper alternative handling. In order to make successful marine pollution prevention, it is necessary to have a good education and outreach program, a reliable system of law and policy, and law enforcement to the government and private sector.